Comparative Study Of Various Chemical Refrigerants For Natural Gas Hydrates Production As Alternative Media For Natural Gas Transportation - Ario Guritno; Slamet Slamet (Jurnal Kimia dan Kemasan, 2018)
Indonesia has been facing natural gas declining problem since 2003, and one of the alternative solutions which can be proposed is by producing gas from the stranded area. Stranded gas is not much developed due to its remote location and a small number of gas reserves. Natural Gas Hydrates or NGH is one of promising alternative medium for natural gas transportation, but it is not much developed yet. Transportation of NGH requires neither cryogenic temperature as LNG does nor high pressure as CNG does. This theoretical study will suggest a simulation scheme to produce synthetic NGH. Production of synthetic NGH utilizes a refrigeration cycle as a cooling source. Based on proposed proses for converting natural gas to NGH, various design parameters for a refrigeration cycle have been investigated. Results obtained suggested that propane as a refrigerant with a specific operating parameter can be a good alternative for the production of NGH.